Kinetic Sand Media to improve Pre-writing in Children with Spastic Type of Cerebral Palsy - Iswari, Mega; Budi, Setia; Arnes, Gaby; Utami, Iga Setia; Triswandari, Retno; Wulandari, Apriani (Journal of ICSAR, 2024)
This study is based on the problems found in SLB 1 Padang Panjang. There is a child with spastic type of cerebral palsy (CP) had low pre-writing ability, this was indicated by the child's difficulty in moving his muscles, so that the child experienced difficulties in the academic field in his writing ability. The purpose of this study is to improve children's pre-writing skills by using kinetic sand for spastic types of cerebral palsy. The method used is single subject research (SSR) with an ABA design. The test uses a pre-writing ability test, which is to assign children to make horizontal, vertical lines, right and left slashes, curved lines up, down, right and left, write the letters c, i, n, v, z, and write their nicknames. The results of data analysis obtained are in A1 with observations for four days of children in pre-writing. the results are 28%. In state B, the child was given an action in his pre-writing ability using kinetic sand media with the implementation for seven days, the result was 78%. Then on A2 carried out for four days without any further treatment using kinetic sand media, the results were 78%. Based on the results of this study indicates that kinetic sand media can improve pre-writing skills in children with cerebral palsy.